If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4=8y-9y+6=
We move all terms to the left:
-4-(8y-9y+6)=0
We add all the numbers together, and all the variables
-(-1y+6)-4=0
We get rid of parentheses
1y-6-4=0
We add all the numbers together, and all the variables
y-10=0
We move all terms containing y to the left, all other terms to the right
y=10
| x=-x²-1 | | 78/u=3 | | 90+2x-10=x+25 | | x+24=6(-x-3)-3 | | 8n=14.4 | | 6=30/y | | r-60=125 | | x+3x+(x-20)=180 | | 123921387129837982173098172098739817398217389712=x+1 | | x=x²-1 | | 4=76/v | | -15m+30=-12m+6 | | 60r=125 | | 23-2t=9 | | 8y+3-y=5+6y+9 | | (X)=x2+6x+9 | | 7x-2(x-6)=7x+24 | | r+60=125 | | 4(w–96)=-24 | | r/125=60 | | h/8+49=55 | | b/4+2=22 | | 5n=60n= | | u+1/2+2u+3/3=u/4 | | 5(x1)=5+12x | | 8y-3-y=5+6y+9 | | 5(3-h)=7+2(h+4) | | 8^2y=6 | | 21-2v=15 | | 3+4m=15=2m | | -2y-9+8y=3(4y-9) | | 13x-6=5x+6x+14 |